In vivo efficacy of artemether-lumefantrine and chloroquine against Plasmodium vivax: a randomized open label trial in central Ethiopia. - Jimee Hwang (Public Library of Science (PLoS), 2013)
Background In vivo efficacy assessments of antimalarials are essential for ensuring effective case management. In Ethiopia, chloroquine (CQ) without primaquine is the first-line treatment for Plasmodium vivax in malarious areas, but artemether-lumefantrine (AL) is also commonly used. Methods and findings In 2009, we conducted a 42-day efficacy study of AL or CQ for P. vivax in Oromia Regional State, Ethiopia. Individuals with P. vivax monoinfection were enrolled. Primary endpoint was day 28 cure rate. In patients with recurrent parasitemia, drug level and genotyping using microsatellite markers were assessed. Using survival analysis, uncorrected patient cure rates at day 28 were 75.7% (95% confidence interval (CI) 66.8-82.5) for AL and 90.8% (95% CI 83.6-94.9) for CQ. During the 42 days of follow-up, 41.6% (47/113) of patients in the AL arm and 31.8% (34/107) in the CQ arm presented with recurrent P. vivax infection, with the median number of days to recurrence of 28 compared to 35 days in the AL and CQ arm, respectively. Using microsatellite markers to reclassify recurrent parasitemias with a different genotype as non-treatment failures, day 28 cure rates were genotype adjusted to 91.1% (95% CI 84.1-95.1) for AL and to 97.2% (91.6-99.1) for CQ. Three patients (2.8%) with recurrent parasitemia by day 28 in the CQ arm were noted to have drug levels above 100 ng/ml. Conclusions In the short term, both AL and CQ were effective and well-tolerated for P. vivax malaria, but high rates of recurrent parasitemia were noted with both drugs. CQ provided longer post-treatment prophylaxis than AL, resulting in delayed recurrence of parasitemia. Although the current policy of species-specific treatment can be maintained for Ethiopia, the co-administration of primaquine for treatment of P. vivax malaria needs to be urgently considered to prevent relapse infections. Trial registration ClinicalTrials.gov NCT01052584.